Co-treatment of industrial air streams using A.O.P. and adsorption processes - P. Monneyron; A. De La Guardia; M. H. Manero; E. Oliveros; M. T. Maurette; F. Benoit-Marquié (International Journal of Photoenergy)
Coupling adsorption with two different photochemical oxidation methods was investigated, in order to treat industrial gaseous effluents containing a low concentration of Volatile Organic Compounds (VOC). Prior to adsorption/photocatalysis cyclic study, new TiO2 based catalysts were prepared by impregnating commercial zeolites in pellets form using a sol-gel technique. Scanning Electronic Microscopy observations linked to BET and adsorption equilibrium measurements of two VOC (1-butanol or BuOH and methyl-ethyl-ketone or MEK) showed that TiO2 happened to fix on the inert binder, without significant modification of support properties. A specific diffusion cell was used to produce dilute polluted air streams for each VOC in dynamic experiments, in which adsorption and photodegradation phases were alternatively carried out. Adsorption/photocatalysis co-treatment unable the total degradation of BuOH, and the regeneration of adsorbent. When using V-UV photolysis, pure zeolites were used, irradiated at 172 nm with an xenon excimer lamp. Excellent results were observed, since a total and rapid degradation was obtained for both VOC, especially thanks to a determining role of ozone.